Uji Prebiotik Mangga Manalagi (Mangifera indica L. var manalagi) Terhadap Pertumbuhan Lactobacillus plantarum Secara In Vitro - Iit Lusif Tsania; Irul Hidayati; Ita Ainun Jariyah (Universitas Al Azhar Indonesia, 2021)
Prebiotics are food ingredients that cannot be absorbed by the host and will be fermented by colonic bacteria into Short-Chain Fatty Acid. Prebiotics can come from various natural ingredients such as wheat, onions, and bananas. Prebiotic food sources can stimulate the growth of probiotic bacteria which are beneficial bacteria for the host, one of which can produce bacteriocins to fight pathogenic bacteria. Manalagi mango (Mangifera indica L. var manalagi) is a fruit that has the potential as a source of prebiotics because it contains prebiotic food requirements, including dietary fiber and carbohydrates. The purpose of this study is to find out the ability or potential of Manalagi mengkal mango as a source of prebiotics by using a prebiotic test based on the growth of BAL is Lactobacillus plantarum in vitro. The design of this study used an experimental laboratory carried out in vitro by making carbon source media with various concentrations of mango flour, then mixed with liquid MRS, and given Lactobacillus plantarum culture which then measured the carbon source medium in the form of TPC. The highest TPC average yield was 1,7 x 1010 CFU/ml is the variation in the concentration of mango flour 6.89%. Based on the results of a prebiotic test with TPC mango flour manalagi mengkal showed its ability as a source of prebiotics by stimulating the growth of BAL (Lactobacillus plantarum).Keywords – Prebiotics, Manalagi mango, Lactobacillus plantarum